Improved liquid phase separation processes for generating biodegradable microspheres loaded with high concentrations of drugs for tumor embolization. Issue 9 (13th June 2019) - Lu, Shoutao; Jun, Zhang; Li, Maoquan; Hou, Wenbo; Yin, Yuxia; Zhou, Chao; Liu, Guang; Duan, Cuihai; Toft, Egon Steen; Zhang, Haijun
ABSTRACT: Drug-eluting microspheres are the most commonly used particulate embolic agents for transarterial chemoembolization of liver tumors. However, drug loading of degradable embolic particles is often insufficient. In the current study, microspheres prepared from poly(D, L-lactic-co-glycolic acid) were investigated as a biodegradable embolic agent for arterial embolization applications. Through modified solvent evaporation and liquid-induced phase separation, high drug loading (as high as 32%) and low solvent residue (as low as 0.03%) was achieved. Degradation performance, 1 H NMR, and the nonsolvent's influence on solvent residue content were assessed. These drug-loading microspheres with biodegradability hold promise for embolization therapies. GRAPHICAL ABSTRACT: